Nodding syndrome: an enigmatic neglected tropical disease, a newly recognized neurodegenerative disorder with regional clusters in East Africa; could it be an early-onset Alzheimer´s disease? - Kitara, David Lagoro; Lemos, Bernardo; Bump, Jesse Boardman (PAMJ Clinical Medicine, 2021)
Nodding Syndrome (NS) is an enigmatic childhood neurological disorder clustered in East Africa. Histo-immunopathological analysis of brains of deceased NS children showed brain atrophy, neurofibrillary tangles, and tau protein deposition mainly in the entorhinal cortex. The aim of this paper is to describe the clinical and neurological presentations, to use Modified Rankin Scale (MRS) to assess disability and observe possible similarities to an early-onset Alzheimer´s disease. Methods: a case-control study involving 21 NS cases, 21 age and sex-matched community controls, 21 younger healthy siblings and 21 biological parents was conducted. Each NS child and controls underwent clinical and neurological examinations and MRS was used to assess the level of disability. Ethical approval was obtained, and STATA version 14.1 was used for data analysis. A p-value less than 0.05 was considered significant. Results: children with NS exhibited significant cognitive disability in many ways, including poor immediate recall (short-term memory) 15/21 (71.4%), disorientation 13/21 (61.9%), muteness 4/21 (19.0%), poor delayed recall 11/21 (52.4%), and poor concentration 9/21 (42.9%). Just over half of NS-affected children 11/21 (52.4%) exhibited abnormal coordination of limb movements, but majority had normal cranial nerves 18/21 (85.7%), slightly less than half had a normal gait 10/21 (47.6%), and no significant association was observed between poor MRS (score ≥2) with; current age (χ2=4.039, p=0.854), underweight (χ2=1.636, p=0.201), age at onset (χ2=10.611; p=0.389), and reported duration of the syndrome (χ2=4.604, p=0.466). Conclusion: clinical and neurological findings suggest cognitive decline is related primarily to disorders of entorhinal cortex similarly observed in early-onset Alzheimer´s disease. It may not be too early to to suggest that NS is an early-onset Alzheimer´s disease. suggest that NS is an early-onset Alzheimer´s disease.